Age, gender, and current living status were associated with perceived access to treatment among Canadians using a cross sectional survey - Catherine W. T. Chan; Amédé Gogovor; Marie-France Valois; Sara Ahmed (BMC, 2018)
Abstract Background Access, particularly timely access, to care is the Canadian public's most important healthcare concern. The drivers of perceived appropriateness of access to care among patients with at least one chronic health condition (CHC) are not, however, well defined. This study evaluated whether personal characteristics, self-reported health status and care received were associated with patients' perception of effective access in managing a chronic illness. Methods The study population (n = 619) was drawn from a representative sample of the adult Canadian population who reported having ≥1 CHC in the 2013-2014 Health Care in Canada survey. Ordinal regression, with the continuation ratio model, was used to evaluate association of perceived level of access to treatment with socio-demographic factors, perceived health status and care utilization experience. Results Factors most closely associated with patients' satisfaction with care access were: age, sex, current cohabitation, care affordability, and availability of support and information to help manage their CHCs. Individuals, particularly females, < 35 years, currently living alone, with poor access to professional support or information and who feel affordability of care has worsened over the past five years were more likely to report a poorer level of treatment access. Conclusions Individuals living alone, who are younger, and women may be especially susceptible to lower perceived access to care of CHCs and a sense of pessimism about things not getting better. Further evaluation of the reasons behind these findings may help develop effective strategies to assist these populations to access the care they need.